Family Characteristics of Stunting in Lebong Regency - Wismalinda Rita; Bintang Agustina Pratiwi; Betri Anita; Nur Hidayah; Fiana Podesta; Sandy Ardiansyah; Aning Tri Subeqi; Sri Lilestina Nasution; Frensi Riastuti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Lebong is the district with the third-highest stunting rate in Bengkulu Province. Family characteristics, especially the mother, can affect the incidence of stunting in children. This study aims to determine the relationship between family characteristics and the incidence of stunting in the Lebong Regency, Bengkulu Province. The study used a case-control approach with a population of all children under five in the Lebong Regency. Sampling using purposive sampling technique obtained as many as 116 people (58 cases and 58 controls). Data were collected using a questionnaire that had passed the validity and reliability test stages. Furthermore, the collected data were analyzed by univariate, bivariate and multivariate (multiple linear regression analysis). Family characteristics, most of the mothers married at the age of 21 years (58.6%), pregnant at the age of 21-35 years (72.4%), Parity (82.8%), Types of Contraceptives IUDs and Injections (90.5% ) Mother's education graduated from high school (51.70%), education graduated from high school (51.70%). The employment of housewives (60.30%) and the number of family members is 2-4 people (81.90%). There is a relationship between maternal age at marriage, gestational age and maternal education with the incidence of stunting in the Lebong Regency. Mother's education is the most dominant factor associated with the incidence of stunting. Stunting prevention can be done by increasing maternal education or providing education to mothers with low education.  Abstrak: Lebong merupakan kabupaten dengan angka stunting tertinggi ketiga di Provinsi Bengkulu. Karakteristik keluarga terutama ibu dapat berpengaruh terhadap kejadian stunting pada anak. Untuk mengetahui hubungan karakteristik keluarga dengan kejadian stunting di Kabupaten Lebong Provinsi Bengkulu. Penelitian menggunakan pendekatan kasus control dengan populasi seluruh balita di Kabupaten Lebong. Pengambilan sampel menggunakan teknik purposive sampling, diperoleh sebanyak 116 orang (58 kasus dan 58 kontrol). Data dikumpulkan menggunakan kuesioner yang sudah melewati tahap uji validitas dan reliabilitas. Selanjutnya data yang terkumpul dianalisis univariat, bivariat dan multivariat (analisis regresi linier berganda). Karakteristik keluarga sebagian besar ibu menikah pada usia ? 21 tahun (58,6%), hamil pada usia 21-35 tahun (72,4%), Paritas (82,8%), Jenis Kontrasepsi IUD dan Suntik (90,5%) Pendidikan Ibu tamat SMA (51,70%),  Pekerjaan Ibu Rumah Tangga (60,30%) dan Jumlah anggota keluarga 2-4 orang (81,90%). Terdapat hubungan antara usia ibu menikah, usia hamil dan Pendidikan ibu dengan kejadian stunting di Kabupaten Lebong. Pendidikan ibu merupakan faktor yang paling dominan berhubungan dengan kejadian stunting. Pencegahan stunting bisa dilakukan dengan meningkatkan Pendidikan ibu atau memberikan edukasi pada ibu yang berpendidikan rendah.